MOLECULAR DIVERSITY ANALYSIS IN RICE GERMPLASM - K. MADHAVI*, D. MOHAN REDDY, P. SUDHAKAR, B.V. BHASKARA REDDY, LAKSHMINARAYANA R VEMIREDDY (The Journal of Research ANGRAU, 2021)
Genetic diversity estimation based on molecular markers provides a reliable measure for the development of desired variety that is not affected by environmental factors. In this study, molecular diversity analysis of 171 rice genotypes with 41 polymorphic SSR markers resulted in the generation of 84 alleles with 2.04 number of alleles per locus with an average Heterozygosity (H) value of 0.41 and polymorphism information content (PIC) value of 0.35. Average genetic diversity (He) was observed to be 0.33. The distance-based neighbor-joining cluster approaches divided the population into three groups.